Evaluation of Acid and Hydraulic Fracturing Treatment in Halfaya Oil Field-Sadi Formation - Jalal Abdulwahid Al-Sudani; Khalid Munaf Husain (Iraqi Journal of Chemical and Petroleum Engineering, 2017)
Sadi formation is one of the main productive formations in some of Iraqi oil fields. This formation is characterized by its low permeability values leading to low production rates that could be obtained by the natural flow.